Pembangunan Ekosistem Laut Berkelanjutan Melalui Keterlibatan Warga Dalam Pengelolaan Hutan Mangrove di Desa Tanjung Rejo - Rachman, Fazli; Yunita, Sri; Manik, Maria Margaretha; Girsang, Okbertus Bilanta; Safitri, Eni; Sabri, Tengku Muhammad; Halizah, Nur; Yasmin, Putri; Juliandi, Juliandi (Department of Pancasila and Civic Education, Universitas Negeri Medan, 2023)
AbstractMarine ecosystem development is a national agenda for implementing sustainable development goals. Utilization of mangrove forest areas into tourist areas. The use of mangrove forests as tourism in Tanjung Rejo Village reflects the development of sustainable marine ecosystems. This qualitative descriptive research aims to involve residents in managing mangrove forests in Tanjung Rejo Village. Research collection techniques used are observation, interviews, and documentation. Data were analyzed using interactive qualitative data analysis techniques to then draw conclusions deductively. Since 2022 Tanjung Rejo Village has become a Mangrove Tourism Village. The potential of mangroves is utilized to become various mangrove tour packages. The potential of mangroves is utilized to become various mangrove tour packages. Mangrove tourism is able to support mangrove ecosystems by involving village communities through creative economic groups of residents who are regularly fostered by multi-stakeholder partners. Awareness of maintaining the quality of marine ecosystems through mangroves, along with increasing the added value of mangroves economically and socially for village communities. Achieving a balance of environmental, economic and social development is the main emphasis point in achieving sustainable mangrove ecosystem development. Mangrove forest management shows the participatory culture of the residents.————AbstrakPembangunan ekosistem laut menjadi agenda nasional implementasi tujuan pembangunan berkelanjutan. Pemanfaatan hutan mangrove menjadi wisata di Desa Tanjung Rejo mencerminkan pembangunan ekosistem laut berkelanjutan. Penelitian deskriptif kualitatif ini bertujuan untuk pelibatan warga dalam pengelolaan hutan mangrove di Desa Tanjung Rejo. Teknik pengumpulan penelitian yang digunakan adalah observasi, wawancara, dan dokumentasi. Data dianalisis menggunakan teknik analisis data kualitatif interaktif untuk kemudian dilakukan penarikan simpulan secara deduktif. Sejak 2022 Desa Tanjung Rejo menjadi Desa Wisata Mangrove. Potensi mangrove dimanfaatkan menjadi berbagai paket wisata mangrove. Wisata Mangrove mampu ekosistem mangrove dengan pelibatan masyarakat desa melalui kelompok-kelompok ekonomi kreatif warga yang secara berkala dibina oleh mitra multipihak. Kesadaran menjaga kualitas ekosistem laut melalui mangrove, seiring dengan peningkatan nilai tambah mangrove secara ekonomi dan sosial bagi masyarakat desa. Pencapaian kesimbangan pembangunan lingkungan, ekonomi dan sosial menjadi titik tekan utama pencapaian pembangunan ekosistem mangrove yang berkelanjutan. Pengelolaan hutan mangrove menunjukan budaya partisipatif warga.